Skrining Senyawa Antiinfeksi dari Spons yang Dikoleksi dari Bunaken, Manado - Astuti, Puji; Alam, Gemini; Pratiwi, Sylvia; Hertiani, Triana; Wahyuono, Subagus (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2003)
The emergence of drug resistant and multidrug-resistant microbes as well as the lack of any current chemotherapy augmented the necessity to search for new and better anti-infective drug.. This study was aim to screen potential antiinfective extracts of sponges collected from Bunaken, Manado and to report on their antibacterial and antifungal properties. Testing for antiinfective agents was conducted using dilution method. Nutrient Agar was used as the testing media and nutrient broth for the inoculation of microorganisms. Staphylococcus aureus, Escherichia coli and Salmonella typhi were used as the testing bacteria and Candida albicans as the testing fungi. Chloramphenicol was used as positive control for anti bacterial activity and Ketokonazol for antifungi. The two acetone extracts tested (MD-01aceton and MD-02aceton), all of them showed inhibition activities. Following partition with chloroform and methanol, all chloroform extracts inhibited the growth of both bacteria and fungi. These extracts then are considered to be potential candidates for further isolation and characterization as antiinfective agents.